Induksi Kalus dan Optimasi Regenerasi Empat Varietas Padi melalui Kultur In Vitro - Purnamaningsih, Ragapadmi (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2006)
A study was conducted at the Tissue Culture Laboratory of ICABIOGRAD, Bogor, to obtain an optimum medium formulation for calli regenerations of for rice varities (Ciherang, Cisadane, IR64, and T-309). The research activities were done in five steps, i.e., callus induction, callus regeneration, shoot multiplication, root formation, and plant acclimatization. The type of explants used in the study was embriozygotic explants. Five media formulations were used for the callus induction, while four media formulations were used for the callus regeneration. The results showed that the best medium formulation for induction of callus formation was MS + 2,4-D 2 mg/l + casein hidrolisat 3 mg/l, while the best medium formulation for callus regeneration was MS + BA 3 mg/l + thidiazuron 0,1 mg/l.